Financial Performance and Profitability as Determinants of Stock Prices in Indonesia - Guasmin Guasmin; Burhanuddin Burhanuddin; Rajindra Rajindra (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study aims to examine the effect of financial performance on stock prices in manufacturing companies within the consumer goods subsector in Indonesia during the 2020–2024 period, with return on assets as a mediating variable. Financial performance is measured using the current ratio, the debt-to-equity ratio, and the total asset turnover. Secondary data were collected from annual reports, financial statements, and historical stock prices, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that the current ratio and total asset turnover have a significant positive effect on profitability, while the debt-to-equity ratio has a significant negative effect. Profitability also has a significant positive effect on stock prices. The direct effect analysis shows that current ratio and total asset turnover significantly increase stock prices, whereas the debt-to-equity ratio is not significant. The indirect effect analysis shows that profitability partially mediates the influence of current ratio and total asset turnover on stock prices and fully mediates the negative influence of debt-to-equity ratio on stock prices. The findings highlight profitability as a crucial link between financial performance and stock price movements, offering strategic guidance for investment and financial policy decisions in dynamic economic conditions.